Measurement uncertainty of the absorbed dose from fabricated Ge-doped optical fibres and nanoDot OSLD in radiotherapy electron beam dosimetry audit - Abdullah, N.; Noor, N. Mohd; Zaman, Z. Kamarul; Zahid, M. Mohammad (Elsevier, 2025)
The use of transfer dosimeters to validate the accuracy of absorbed dose delivery during radiotherapy dosimetry audits requires estimation of the measurement uncertainty to ensure that the tolerance limits are met. Previous studies have explored the measurement uncertainties in absorbed dose for both Germanium-doped optical fibre (GedOF) and nanoDot optically stimulated luminescence (OSL) dosimetry systems in radiotherapy dosimetry audits involving photon and electron beams. However, there is a paucity of research comparing the detailed measurement uncertainty between GedOF and OSLD, particularly for radiotherapy electron beam dosimetry audits. In this study, the measurement uncertainties in the analysis of the absorbed dose measured from two types of GedOF in cylindrical (CGedOF) and flat (FGedOF) shapes were investigated in comparison with nanoDot OSL dosimeter (OSLD). The uncertainty was derived from two components: (i) the calibration of the dosimeters against the ionization chamber in electron beams based on the IAEA's TRS No. 398, and (ii) the calculation of the absorbed dose to water for each dosimeter, which includes the correction factors of response sensitivities, dose-response linearity, signal fading, and beam energies. Each source of uncertainty was expressed as a relative standard uncertainty, which was classified as type A (random) or type B (systematic). The total combined standard uncertainty was calculated by summing the Type A and Type B uncertainties using a quadratic method. The largest relative standard uncertainty in the absorbed dose measurement from each dosimeter arose from the calibration coefficient of these dosimetry systems (1.32 %–1.36 %), followed by the stability of the TLD/OSLD reader long term stability (0.47 %–0.52 %) and statistical TL/OSL readings (0.38 %–0.59 %). The quadratic summation of all relative standard uncertainties resulted in total combined uncertainties of 1.31 % for CGedOF and 1.36 % for both FGedOF and OSLD, resulting in tolerance limits of 3.93 % for CGedOF and 4.08 % for both FGedOF and OSLD. In conclusion, this study provides valuable insights into the measurement uncertainties of both CGedOF and FGedOF in radiotherapy applications, highlighting their potential as reliable tools for dose verification in remote dosimetry audits.